Pengembangan Sistem Absensi Digital Karyawan Menggunakan Teknologi PHP dan MySQL, Bawaslu Provinsi Papua Tengah - Paulus S Deda; Immanuel Candra Irawan (Jurnal Teknologi dan Informatika, 2026)
This research is motivated by the problem of inefficient manual recording of employee attendance at the Central Papua Provincial Bawaslu, which often causes errors and inaccurate attendance data. The main goal of the research is to develop a PHP and MySQL-based digital attendance system that is able to record attendance automatically, real-time, and integrated. The research methods include needs analysis, database and interface design, program code implementation, and system testing. The results of the study show that the digital attendance system developed has succeeded in facilitating the recording of entry times, exit times, and recapitulation of employee attendance with a higher level of accuracy than manual methods. The implications of the implementation of this system are increased administrative efficiency, ease of monitoring, and the provision of more valid attendance data to support fast and appropriate decision-making within the Central Papua Provincial Bawaslu. Thus, this digital attendance system can be a practical solution in improving the quality of human resource management in government agencies.